Nanjing: Historical Landscape and Its Planning from Geographical Perspective - Yao, Yifeng (Springer Geography, 2016)
This book studies the historical changes of the cityscape of Nanjing from the point of view of geographical systems. Nanjing is a city located along the Yangtze River, originated 2500 years ago, after which ten dynasties established their capital dependent on the geographical conditions. The book focuses on the analysis of the characteristics of mountain and river systems in the various historical periods, and provides investigations of historical sites along with these systems. This enables the search for the laws of historical evolution and spatial structure changes, which is also the research of the relationship between man and nature. It extends the traditional preservation and cityscapes planning to that of geographical landscape system. Readers working in the area of geography, history, urban and landscape planning will benefit from it.